Los ingresos y gastos y su incidencia en la rentabilidad de la constructora Chalett S.A. Cochaletsa, periodo 2019 – 2020 - Paz Sánchez, Dayana Michel (2021)
The following case study called "Income and expenses and their impact on the profitability of the construction company Chalett S.A. Cochaletsa, period 2019 - 2020" was developed in order to show how the income and expenses of the company affect the profitability obtained in the periods mentioned above, with the problem existing in the period 2019 where the entity does not have the existence of income due to poor management at the time of obtaining the works that are presented to it. For the development of this study, techniques such as interviews were used, which allowed gathering sufficient and adequate information for the execution of the study, as well as the application of financial tools that allowed evaluating the impact of income and expenses on profitability, as is the case of the financial ratios known as profit margin, ROA, ROE, current ratio, cash ratio, total debt ratio and the turnover rate of accounts receivable and days of sales in accounts receivable. In addition, the use of horizontal analysis was used to see the variations of the company's income and expenses with respect to the years 2019 and 2020. Of the two periods analyzed, the most complex was 2019, since the construction company was affected by the non-existence of income, which resulted in the company incurring losses for that year, since there were expenses that, despite the non-existence of works, are obligatorily incurred, as is the case of administrative expenses, this situation affected the profitability of the entity as evidenced in the application of the financial ratios.